Critical thinking in respiratory care practice - Shelley C. Mishoe; Bradley C. Courtenay (Adult Education Research Conference, 1994)
The purpose of this study was to identify and describe the reflective, communicative, practical and experiential aspects of critical thinking (CT) in respiratory care practice using a qualitative research methodology. Critical thinking is described in terms of practical knowledge grounded within the actual performance, culture and context of clinical practice.